Logically Correct Argument Tu Quoque - Sękowski, Piotr M. (Hybris, 2019)
The argument tu quoque is widely called a logical fallacy. The aim of this study is to show, that this theorem is ill-considered. The text is focused on the analysis of various examples of tu quoque. This analysis leads to the conclusion that there are logically correct tu quoque. There are given some examples of such tu quoque. Main theorem of the article is that tu quoque is correct if it’s used as some kind of mental shortcut referring to other arguments.